Morphological structure of Nisgha - Azak, Bertha; Doolan, Dorothy (1986)
Linguistic field recordings of the Nisgha (Nisga'a, Niska) language. Elicitation of a numbered list of words and phrases conducted by Linda Walsh with consultants Dorothy Doolan and Bertha Azak. Recorded from 1986 to 1987 in Vancouver, British Columbia.